Are patient-reported outcomes the same following second-side surgery in primary hip and knee arthroplasty?. (1st April 2021) - Tucker, Adam; Warnock, Jonathan M.; Cassidy, Roslyn; Napier, Richard J.; Beverland, David
Abstract : Aims: Up to one in five patients undergoing primary total hip (THA) and knee arthroplasty (TKA) require contralateral surgery. This is frequently performed as a staged procedure. This study aimed to determine if outcomes, as determined by the Oxford Hip Score (OHS) and Knee Score (OKS) differed following second-side surgery. Methods: Over a five-year period all patients who underwent staged bilateral primary THA or TKA utilizing the same type of implants were studied. Eligible patients had both preoperative and one year Oxford scores and had their second procedure completed within a mean (2 SDs) of the primary surgery. Patient demographics, radiographs, and OHS and OKS were analyzed. Results: A total of 236 patients met the inclusion criteria, of which 122 were THAs and 114 TKAs. The mean age was 66.5 years (SD 9.4), with a 2:1 female:male ratio. THAs showed similar significant improvements in outcomes following first- and second-side surgery, regardless of sex. In contrast for TKAs, although male patients demonstrated the same pattern as the THAs, female TKAs displayed significantly less improvement in both OKS and its pain component following second-side surgery. Conclusion: Female patients undergoing second-side TKA showed less improvement in Oxford and pain scores compared to the first-side. This difference in outcome following second-side surgery did not apply to male patients undergoing TKA, or to either sex undergoing THA. Cite this article: Bone Jt Open 2021;2(4):243–254.